Characteristics of Liposarcoma Patients: 5-Year Data - Rahmah, Miftahur; Afiati, Afiati; Sugiri, Unwati (Althea Medical Journal, 2018)
Background: Liposarcoma is the second highest soft tissue sarcoma in adults with prevalence of 15% to 25%. If the size of liposarcoma is very large, it may cause abdominal pain, weight loss, gastrointestinal bleeding, even kidney failure. Therefore, for early detection of liposarcoma, the characteristics of liposarcoma should be investigated. This study aimed to determine liposarcoma characteristics based on age, sex, location and histopathologic type according to WHO (World Health Organization) Classification of Tumors 2013.Methods: A descriptive study was conducted from August to October 2015 at the Department of Anatomic Pathology, Dr. Hasan Sadikin General Hospital, Bandung, Indonesia. Data was obtained from database of patients with liposarcoma at the Department of Anatomic Pathology in the period of January 2010 to December 2014. The collected data was presented in the form of figures and tables.Results: Out of 102 cases, the percentage of liposarcoma was highest between the age of 50 and 59 years (31.37%), followed by the age of 40â49 years (28.43%). The percentage were slightly higher in males (54.9%) compared to females with a ratio of 1.22:1. Femur (23.52%), intraabdomen (22.55%) and retroperitoneum (11.76%) were the most common locations affected. The most common histopathologic subtype was myxoid liposarcoma (52.95%) exceeding a half of the total cases.Conclusions: Liposarcoma most likely occurs in the age range of 40â60 years, the percentage is slightly higher in males, and abdomen and lower extremities are the most common location affected. Myxoid liposarcoma is the most common subtype.Â